Transcultural psychotherapy as a process of symbolic co-construction in clinical relation : the cultural and migration dynamics in a case of attempted suicide - E. F. M. Riva (2009)
Transcultural psychiatry and psychotherapy are gaining space and relevance in Italy, both in private profession and in public services’ clinical treatment, where we encounter, thanks to the variety and the heterogeneity of the migratory flows that have invested our country in last the 30 years (Caritas, 2008, Ismu, 2008) persons with various historico-cultural characteristics, migratory percourses and intrasomatic cultures (Inghilleri, in press). Therefore the Italian Transcultural Clinical Modelsthath takes origins both from the Canadian school of Mc the Guill University and from the French School of Nathan and Moro, is developing and consolidating more flexible diagnostic and therapeutic models (Terranova, in press course), that take in account both the variability of the cultural paradigms of the single patients and the specific characteristics of the territorial services, adapting themselves to them and constructing individualized therapy percourses, also from the point of view of the setting construction and of the transcultural instruments selection. Objective of my intervent will be to expose, through the presentation of the case of a young adolescent recently immigrated from Ghana, brought in urgency to Niguarda Hospital after an attempted suicide, some of the diagnostic and therapeutic instruments promoted from the School of Transcultural Psychoterapy of Milan (Fondazione Cecchini-Pace), like the analysis and the use of the artefacts (Vigotskij 1934, Monod 1970; Nathan 1993; Inghilleri, 2003), the cultural resistance (Reidd, 1999), the metapsychic guarantors (Kaes, 1993; 2007), the cultural mediator (Luatti, the 2006) and the open transcultural setting. In conclusion, it will be also shown their practical effectiveness both in the differential diagnosis and in the successive therapeutic process.